2023
DOI: 10.1093/jxb/erad165
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide promotes tolerance to drought through protein persulfidation in Arabidopsis

Abstract: Hydrogen sulfide (H2S) is a signaling molecule that regulates essential plant processes. In this study, the role of H2S during drought was analyzed, focused on the underlying mechanism. Pretreatments with H2S before imposing drought on plants significantly improved the characteristic stressed phenotypes under drought and decreases the levels of typical biochemical stress markers such as, anthocyanin, proline and hydrogen peroxide. H2S also regulated drought-responsive genes, amino acid metabolism, and represse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…This whole model was very recently corroborated by Jurado-Flores et al [105]: the authors showed that the pre-treatment of Arabidopsis plants with H 2 S donors significantly diminishes the levels of several drought biomarkers (such as proline, H 2 O 2 and anthocyanins), but they also highlighted the H 2 S-mediated protein persulfidation as a crucial molecular defense mechanism against drought stress.…”
Section: The Role Of Cysteine Metabolism In Drought Stress Responsementioning
confidence: 55%
“…This whole model was very recently corroborated by Jurado-Flores et al [105]: the authors showed that the pre-treatment of Arabidopsis plants with H 2 S donors significantly diminishes the levels of several drought biomarkers (such as proline, H 2 O 2 and anthocyanins), but they also highlighted the H 2 S-mediated protein persulfidation as a crucial molecular defense mechanism against drought stress.…”
Section: The Role Of Cysteine Metabolism In Drought Stress Responsementioning
confidence: 55%
“…In addition, these various mechanisms by which intracellular H 2 S affects physiological processes often exist simultaneously. For instance, in plants, H 2 S not only regulated transcription levels of drought-responsive genes but also induced the persulfidation level of proteins, which involved in cellular response to oxidative stress, hydrogen peroxide catabolism and so on, to involve in drought stress responses 43 . Therefore, further research is needed to clarify regulatory mechanisms of H 2 S on cellulase activity in G. lucidum .…”
Section: Discussionmentioning
confidence: 99%
“…For example, under salt stress, H 2 S triggers PMA1 to sustain the K + /Na + balance by means of persulfidation [11]; nitrate reductase 2 (NIA2) persulfidation is involved in OsLCD1-regulated drought tolerance in rice [22]. Proteomic analysis showed that the enriched motif containing the most persulfidated proteins (11) is involved in the cellular response to oxidative stress in Arabidopsis under drought stress (Table 1), containing numerous antioxidant enzymes [47]. A similar situation occurs in tomato, where, in response to oxidative stress induced by the phytotoxicity of CuO NPs, H 2 S responds to stress by nondirectionally regulating the activities of POD, CAT, and APX by means of persulfidation [48]; these effects seem to be the consequence of increased ROS contents, especially that of H 2 O 2 .…”
Section: Post-translational Modification (Ptm) Of Cysteine Residues B...mentioning
confidence: 99%